PERKEMBANGAN GABUNGAN POLITIK INDONESIA (GAPI) PADA MASA PERGERAKAN NASIONAL INDONESIA 1939-1942 - Maretha Yolanda; Umi Hartati (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
The purpose of this study is to analyze and describe the development of the Indonesian Political Association during the Indonesian national movement in establishing parties and joining the Gapi. The research method uses historical research methods with steps such as heuristics, literature study, the validity of data collection tools and data analysis methods. The research resulted in the development of the Indonesian Political Association during the Indonesian national movement followed by various political parties that were established in Indonesia such as Parindra, Gerindo, Pasundan, PSI, and PSII. All of these parties joined Gapi, of course, to achieve the goal of the Indonesian nation that had been expected, namely Indonesia with a parliament. This is certainly an attraction for members or political parties to join the organization. Gapi's goal is to make Indonesia a parliamentary country. However, the government did various things that were intended to hinder every step taken by the nationalist figures. Therefore, there were several parties that finally followed the wishes of the Dutch by being cooperative. Characters who play a role in Gapi include Mohammad Husni Thamrin, Mr. Syarufuddin Prawiranegara, and Abikusno Cokrosuyoso who served as chairman, general writer, and treasurer. However, because of the nation's persistence towards its goals, this organization persisted until the establishment of the Indonesian People's Congress and the Indonesian People's Assembly and this organization continued to exist until Indonesia was occupied by Japan and then all political organizations in Indonesia were dissolved by the Japanese except MIAI.